Qur'anic Narratives on Nature and Ecological Activism in Indonesia - Suyuti Dahlan Rifa’i; Agiel Laksamana Putra; Nawwira Zakiyatuzzahro; Triana Zio Khapizah (Jurnal Lentera Insani, 2025)
Departing from the ecological crisis that reveals the paradox between ritual piety and massive environmental destruction, this study positions the Qur'anic narrative about nature not as a frozen normative text, but as a living ethical-political horizon with the potential to convert Indonesian Muslim religiosity into transformative ecological activism. This study uses a qualitative approach with an interpretive-critical design, combined with a multiple-case study strategy, to examine in depth how the Qur'anic narrative about nature is produced, articulated, and mobilised in ecological activism as a social practice rich in context, values, and power relations. The results indicate that the reconstruction of Qur'anic narratives about the cosmos, mīzān, fasād, raḥmah, and amānah of the caliphate encourages the conversion of religiosity from ritualistic to ecological religiosity, which positions nature as an ethical-political subject, while also providing a framing device for Muslim activists, Islamic boarding schools, and grassroots movements to build awareness, environmentally friendly practices, and advocacy for ecological justice in agrarian conflicts, climate crises, and resource management. These findings strengthen and expand the study of Islam and the environment by showing that Qur'anic narratives function as symbolic resources that frame awareness, build solidarity, and drive community-based ecological activism, especially when they engage creatively with local wisdom and respond to the dynamics of environmental politics in Indonesia.